Policy Analysis on The Arrangement of Street Vendors (Literature Study In Sidoarjo Regency) - Risma Pratiwi; Hendra Sukmana (Jurnal Ad'ministrare, 2022)
This research is a literature study on government policy. This study aims to discuss what street vendors can do to maintain their business during the covid-9 pandemic. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is divided into primary data and secondary data. Sources of data obtained through Library Research are sources available online and offline, such as scientific journals, books, and news from trusted sources. The results of the study concluded that controlling the main road for Taman Pinang Housing, Sidoarjo Regency, and local SKPD by applicable regional regulations. These regional regulations include Regional Regulation No. 2. 2. Regional Regulation Number 10 of 2013, Regional Regulation Number 3 of 2016, and Regional Regulation Number 3 of Sidoarjo Regency. 188/455/404.1.1.3/2017. Obstacles faced by local governments include poor policy enforcement, inadequate strategic relocation solutions, pressure groups, illegal street vendors who are reluctant to move, and limited budgets.